GEOMETRIC PARAMETERS DETERMINATION AND SIMULATION OF SMALL-SIZED RV REDUCER - WANG Jun; ZHANG HuiMin (Jixie qiangdu)
At present, more and more small-sized or even micro reducers are applied in the fields of national defense and military, medical equipment, aerospace, etc. In view of the large size of the current RV reducers, a small-sized RV Reducer is proposed. Firstly, based on the analysis of the basic structure of the small-sized RV Reducer, the size parameters of each part were determined, and the 3 D solid model was established by SolidWorks software. Then, the force analysis and strength check of the involute planetary gear and cycloid pin gear mechanism were carried out by the theory of force analysis and strength check for conventional RV transmission system, and the simulation is carried out by the finite element analysis software. Finally, by comparing the theoretical calculation results with the simulation results, the maximum contact stress errors of the involute planetary gear and the cycloidal pin gear tooth surface are up to 5.77% and 11.03%, respectively, which verifies the correctness of the theoretical analysis and the rationality of the structural design, and provides theoretical support for the subsequent research on small-sized RV reducers.